1994
DOI: 10.1080/07391102.1994.10508039
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Two Peptide-Acridine Conjugates Containing the SPKK Peptide Motif with DNA and Chromatin

Abstract: The interaction between DNA and two peptide-acridine conjugates containing one (1) or two (2) moieties of the Ser-Pro-Lys-Lys (SPKK) minor groove-binding peptide motif has been studied by a combination of hydrodynamic, biochemical and spectroscopic methods including diffusion-enhanced luminescence energy transfer (DELET) measurements with a Tb(III) lanthanide chelate as donor. Viscometric titrations do not reveal any significant difference between the two hybrid molecules which both unwind (by about 15 degrees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Linear dichroism provides a sensitive tool to define the orientation of drugs bound to DNA (Norden et al, 1992) and has the additional advantage that it senses only the orientation of the polymerbound ligand: free ligand is isotropic and does not contribute to the signal. We have shown that electric linear dichroism can be particularly useful as a means of analyzing the structure of hybrid molecule-DNA complexes (Bailly et al, 1990(Bailly et al, , 1992a(Bailly et al, , 1993aFlock et al, 1994). Figure 8a shows the ELD spectra of complexes of Distel (1+) and Distel (2+) with poly(dA-dT)*poly(dA-dT).…”
Section: Resultsmentioning
confidence: 99%
“…Linear dichroism provides a sensitive tool to define the orientation of drugs bound to DNA (Norden et al, 1992) and has the additional advantage that it senses only the orientation of the polymerbound ligand: free ligand is isotropic and does not contribute to the signal. We have shown that electric linear dichroism can be particularly useful as a means of analyzing the structure of hybrid molecule-DNA complexes (Bailly et al, 1990(Bailly et al, , 1992a(Bailly et al, , 1993aFlock et al, 1994). Figure 8a shows the ELD spectra of complexes of Distel (1+) and Distel (2+) with poly(dA-dT)*poly(dA-dT).…”
Section: Resultsmentioning
confidence: 99%
“…The design of drugs linked to Lys-containing di- and tripeptides is also considered. In the past, we also successfully elaborated peptide−intercalator conjugates encompassing one or two Ser-Pro-Lys-Lys (SPKK) motifs ( ). The same motif could also be adequate to optimize the activity of the oxoazabenzo[ de ]anthracene ring system.…”
Section: Discussionmentioning
confidence: 99%
“…Both peptide conjugates interact with the major and minor grooves of dsDNA. This process is not impacted by the interaction of the dsDNA with histones [85,86]. However, the probability of the SPKKSPKK octapeptide binding to the minor groove of dsDNA depends on the (non-)availability of histone proteins [87].…”
Section: Short Peptides + Dnamentioning
confidence: 99%